Pathophysiology in Systemic Sclerosis: Current Insights and Future Perspectives - Suzan Al-Gburi; Pia Moinzadeh; Thomas Krieg (Sclerosis)
Background: Systemic sclerosis (SSc) is a rare connective tissue disease characterized by vasculopathy, autoimmunity, and fibrosis. Due to its low prevalence and heterogeneous clinical presentation, early diagnosis remains challenging, often delaying appropriate treatment. The disease progresses from microvascular dysfunction, manifesting as Raynaud’s phenomenon, to systemic fibrosis affecting multiple organs, including the lungs, gastrointestinal tract, heart, and kidneys. There have been considerable advancements in understanding the pathophysiology of the disease during the last few years and this has already resulted in the improvement of the therapeutic approaches used to control organ-specific manifestations. However, the underlying cause of the disease still remains incompletely elucidated. Methods: Here, we summarize the current knowledge on the SSc pathogenesis. Results: The pathophysiology involves an interplay of chronic inflammation, impaired vascular function, and excessive extracellular matrix deposition, leading to progressive organ damage. Endothelial dysfunction in SSc is driven by immune-mediated injury, oxidative stress, and the imbalance of vasoconstrictors and vasodilators, leading to capillary loss and chronic hypoxia. Autoantibodies against endothelial cells or other toxic factors induce apoptosis and impair angiogenesis, further exacerbating vascular damage. Despite increased angiogenic factor levels, capillary repair mechanisms are defective, resulting in progressive ischemic damage. Dysregulated immune responses involving Th2 cytokines, B cells, and macrophages contribute to fibroblast activation and excessive collagen deposition. Transforming growth factor-beta (TGF-β) plays a central role in fibrotic progression, while fibroblasts resist apoptosis, perpetuating tissue scarring. The extracellular matrix in SSc is abnormally stiff, reinforcing fibroblast activation and creating a self-perpetuating fibrotic cycle. Conclusions: Advances in molecular and cellular understanding have facilitated targeted therapies, yet effective disease-modifying treatments remain limited. Future research should focus on precision medicine approaches, integrating biomarkers and novel therapeutics to improve patient outcomes.